Juridical Review of Decision Number 809/PID.SUS/2024/PN DPS Related to the Protection of Protected Animals in Review Based on the Law on Conservation of Natural Resources and Ecosystems - I Kadek Krisna Paradipta; H. Nurianto RS; Komang Edy Dharma Saputra (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This research discusses the legal protection of protected animals under the Law on Conservation of Living Natural Resources and Ecosystems in Indonesia. The existence of protected animals is increasingly threatened, so an understanding of the applicable law is important to prevent violations. The objectives of this study are to (1) determine the legal protection of protected animals, and (2) evaluate the legal consequences of Decision Number 809/PID.SUS/2024/PN DPS on the protection of protected animals. The research method used is normative legal research with a statutory approach, case approach, and conceptual approach. Data collection was conducted through a literature study that involved reading, reviewing, and recording relevant legal sources. The results showed that the legislative framework in Indonesia for the protection of protected animals is regulated in Law No. 5 of 1990, which has been amended into Law No. 32 of 2024. Decision number 809/PID.SUS/2024/PN DPS shows that there are positive and negative impacts on animal protection, where although there are considerations of justice, there is potential for future law violations. This research concludes that the legal protection of protected animals in Indonesia requires strengthening in law enforcement and increasing public awareness. Recommendations are proposed to increase socialization on the types of protected animals and the sanctions that apply to violations.